EVALUASI USER EXPERIENCE PADA SISTEM INFORMASI WISUDA (SIUDA) UPN VETERAN JAKARTA DENGAN METODE USER EXPERIENCE QUESTIONNAIRE (UEQ), COGNITIVE WALKTHROUGH (CW), DAN HEURISTIC EVALUATION (HE) - Nabilah Luthfiana Putri, (2023)
The Graduation Information System (SIUDA) of UPN Veteran Jakarta is one of UPN Veteran Jakarta's systems that provides information related to graduation, which has been used since 2019 for managing and registering graduation within the UPNVJ environment. From interviews, observations, and pre-research questionnaires, several issues were identified, such as stacked and hard-to-read information, non-responsive interface, monotonous design, mismatched information structure, and more. Therefore, an evaluation of SIUDA UPNVJ is necessary to assess user experience. The evaluation employed User Experience Questionnaire (UEQ) with 400 respondents, Cognitive Walkthrough (CW) with 5 evaluators, and Heuristic Evaluation (HE) with 2 UI/UX experts. The UEQ evaluation indicated that the Perspicuity scale was Above Average (mean 1.10), while Attractiveness (mean 0.86), Efficiency (mean 0.78), Dependability (mean 0.94), and Stimulation (mean 0.63) were Below Average, and Novelty (mean -0.05) was rated as Bad. The CW evaluation showed an ORE metric score of 71% for all task scenarios, with one scenario scoring 0% for the Download Graduation Book feature. The HE evaluation identified 7 problems as Usability Catastrophe, 9 as Major Usability Problems, 5 as Minor Usability Problems, and 5 as Cosmetic Problems. Design improvements were made focusing on the four elements of UX: Branding, Content, Functionality, and Usability.